STRATEGI PENGAWASAN LURAH TERHADAP EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN LAWAWOI KABUPATEN SIDENRENG RAPPANG - Evi Evi; Herman Dema; Muhammad Rusdi (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Thepurpose ofthis researchis to determine theLurah SupervisionStrategy on the Effectiveness of Land and Building Tax (PBB) collection in Lawawoi Village, Sidenreng Rappang Regency. The population taken in this study were all household heads in the Lawawoi Village, Sidenreng Rappang Regency, as many as 859 households and a sample of 86 households. The sampling technique used is probability sampling. Thistype ofresearch isdescriptive quantitative. Datacollection techniques are observation, interview, questionnaire (questionnaire) and literature study. Thedata analysis technique usedin this studywas descriptive statistics. Based on research that is taken from the results of the questionnaire, it is obtained that the recapitulation of variable X (Supervision Strategy) reaches a value of 75.5% including the